Preparation and Release Mechanism of Natural-Skeleton Sustained-Release Tracer Particles - Liu, Yufei (Scientific Journal of Technology, 2026)
In the current field of petroleum development, water-source identification and water shutoff in horizontal wells have become key difficulties affecting the sustained development of such wells. Intelligent tracer-based water diagnosis and shutoff technology can provide highly intuitive information on the location and intensity of water production along the horizontal section and therefore has broad development prospects. However, the long-term performance of intelligent tracer-based water shutoff in horizontal wells is influenced by many factors, such as erosion by formation fluids and aging of shutoff materials. In field applications, effective methods for monitoring and evaluating the long-term effect of water shutoff treatments are still lacking, making it difficult to accurately judge their long-term effectiveness. A better understanding of the dominant factors controlling the sustained-release behavior of intelligent tracers, and further optimization of that behavior, is a prerequisite for subsequent intelligent tracer-based water-control operations in horizontal wells. Therefore, taking a self-developed water-soluble intelligent tracer as the research object, this paper investigates its macroscopic physical properties and microstructure by CT scanning. Based on the characteristics of its physical skeleton, a suitable sustained-release tracer was selected, and static scouring experiments were carried out. The sustained-release behavior was qualitatively analyzed from four aspects: scouring flow rate, temperature, particle diameter, and active-component content. The static scouring experiments demonstrate that this natural skeleton can realize rapid tracer release and satisfy the requirement of sensitivity to water-flow velocity. The experiments also show that scouring flow rate and temperature are the main factors affecting sustained-release performance; within an appropriate range, higher temperature and higher scouring flow rate accelerate the release process. Particle diameter and active-component content are not the dominant control factors. Among the four factors, scouring flow rate has the strongest effect. Under a certain scouring rate, the tracer component stored inside the skeleton can be released rapidly, and the release efficiency can approach 100%. The results indicate that this intelligent tracer can be released rapidly in the short term and is highly sensitive to water-flow velocity. It can provide a rapid evaluation tool for subsequent field water-finding and water-shutoff operations, and it also provides a reference for selecting skeleton materials and tracer components for sustained-release tracer particles and for interpreting tracer-concentration curves.